Morphological studies of Enterolobium schomburgkii Benth. (Leguminosae-Mimosoideae) fruits, seeds and seedlings - Ramos, Michele Braule Pinto (2008)
Enterolobium schomburgkii Benth. ("orelha-de-macaco") is a valuable shade intolerant timber species, because it produces nodules, it has a great potential for plantation in degraded areas. The objective of this propagation study was to describe morphologically fruits, seeds and seedlings and define the "normal seedling" of E. schomburgki in order to provide important information for the development of seed technology. The fruit is a nutant legume, sub woody, polyspermic, with strombus and circular form. The dimensions of the fruit are 21.2 x 3.2 cm as extended legume and 6.2 x 5.9 x 0.5 cm in original form. Fresh weight of fruit averaged 6.7 g, with 16.1 healthy seeds per fruit; 62 fruits contain 1,000 healthy seeds. The number of fruit per kilogram was 18,749 and the weight of 1,000 seeds was 53.6 g. The seed is elliptic, with soft surface, brightness, dark yellowish brown, with size of 8.0 x 3.9 x 2.6 mm and fresh weight averaging 0.054 g. The embryonic axis is rectilinear and visible, with plumule well developed. The germination is epigeous phanerocotyledonary, with foliaceous cotyledons. Root protrusion averaged 95.7%, and 80.2% for normal seedling formation. The "normal seedling" was developed 7 to 15 days after sowing, with primary root well developed, secondary roots small, long hypocotyl, semi-open cotyledons and first leaf visible, with the same size of cotyledons.